2006
DOI: 10.1021/jp055697v
|View full text |Cite
|
Sign up to set email alerts
|

Better Chemistry through Ceramics:  The Physical Bases of the Outstanding Chemistry of ORMOSIL

Abstract: Twenty years after their invention, sol-gel organically modified silicates (ORMOSIL) are finding a number of impressive applications that range from efficient deliver of genes into mouse brains to self-ordered helices of interest to fields as diverse as optics, catalysis, molecular recognition, and chromatography. The physical bases of this mulifaceted chemistry, therefore, are of immense importance to scientists working toward new applications such as photovoltaics and catalysis that are crucially important i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 60 publications
1
61
0
Order By: Relevance
“…[19,[23][24][25]27] We tried to do the same; first cyclam was entrapped and then efforts to complex it with Ni 2 + were performed. Even under extreme conditions (two weeks reflux in methanol and tenfold excess of the nickel ion) the solid matrix did not change its color.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19,[23][24][25]27] We tried to do the same; first cyclam was entrapped and then efforts to complex it with Ni 2 + were performed. Even under extreme conditions (two weeks reflux in methanol and tenfold excess of the nickel ion) the solid matrix did not change its color.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of R' groups to the surface decreases the polarity of the pore walls, because the number of silanol groups on the surface decreases and shielding of the remaining silanol groups can also occur. [15,27] The hydrolysis of ORMOSILs is slower relative to that of Si(OR) 4 , and the R'Si(OH) 3 monomers formed slowly condense fast to form micellar like structures. Pagliaro et al have shown that matrices made only from TMOS have structures that contain mainly four-membered rings.…”
Section: Entrapment Of Nickel(iimentioning
confidence: 99%
“…However, a possible route to lower process costs is to minimize the consumption of catalyst. Cririminna et al reported the use of platinum nanoparticles incorporated into a silicate porous matrix for the hydrosilylation of long-chained alkenes (Figure 42) [122]. The benefit of the system is the minimized leaching of catalyst during reaction, preventing loss of the catalyst and contamination of the product.…”
Section: High Efficient/low-cost Hydrosilylation (Solvent-free Conditmentioning
confidence: 99%
“…[12] (2) The electrode can operate in a medium in which the electrocatalyst is insoluble and/or unstable. [2,12b] The applications of these matrices in electrocatalysis are limited, because the matrices are insulators [13] and therefore the plausible current densities are low. [14] Furthermore, the diffusion of the substrate to the electrocatalyst is slow.…”
Section: Introductionmentioning
confidence: 99%